FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP REMAJA PADA BUDAYA KOREAN POP DI KOTA SURABAYA - Yodiva Fitri Amalia; Didik Tranggono (Universitas Prof. Dr. Moestopo (Beragama), 2022)
At present the global influence in the spread of culture is increasingly visible due to various factors. Supporting factors such as social media and mass media. In the development of the phenomenon of K-Pop (Korean Pop) or the wave of the Korean Wave in Indonesia, this has led to the emergence of many communities of lovers of K-Pop artists, especially for teenagers, of course many have formed a community so that they can share information or knowledge about the Korean Wave. Korean pop culture is highly accepted by teenage fan groups in the city of Surabaya. The purpose of this study is to determine the effect of role models and the expression of idolization of Korean pop culture on adolescent attitudes in the city of Surabaya. The theory used is Korean pop culture which consists of Role Models and Expression of Idoltation. Besides that, it also uses the theory of adolescent attitudes. The research method used in this research is quantitative. With data collection techniques through the distribution of questionnaires/questionnaires. The results of this study show the results of multiple linear regression analysis, the dimension of Korean pop culture that has the greatest influence on adolescent attitudes in the city of Surabaya is role mode with an overall indicator mean of 2.95. Then the results of the hypothesis test show that the influence given by Korean pop content culture on adolescent attitudes in the city of Surabaya has an influence of 81%.